ANALISIS PSYCHOLOGICAL SAFETY CLEANING SERVICE OFFICER PADA ERA FIESTA PROPERTY KABUPATEN TANGERANG - Deo Resta Putra; Fauziah Septiani (Yayasan Education and Social Center, 2026)
Success: This study analyzed the level of psychological safety among Cleaning Service Officers (CSOs) at Era Fiesta Property. The CSO unit plays a vital role but is vulnerable to a low sense of psychological safety due to its hierarchical position. Using qualitative methods through in-depth interviews with 12 informants, this study measured four key indicators: courage to speak up, tolerance for mistakes, self-disclosure, and a sense of being valued within the team. The primary objective was to understand how the work climate influences staff's courage in reporting problems and making efficiency suggestions. The results showed that the company successfully built a positive psychological safety climate through an educational management approach and strong team solidarity. Senior employees had a high level of confidence to innovate and report errors without fear due to the support of their superiors. However, challenges were encountered among new employees, who tended to hold back due to feelings of embarrassment. In conclusion, the strategy of humanizing employees has been effective for long-standing staff, but the company needs to increase inclusivity in the new employee orientation process to accelerate the development of psychological safety.